Evaluating the Quality of Websites of Research Institutes Affiliated to Iranian Universities of Medical Sciences - Rezvan Ansari; Reza Khajouei (مدیریت اطلاعات سلامت, 2016)
Introduction: Websites of university research institutes play an important role in communicating and providing services to their users. The aim of this study was to determine the quality of websites of research institutes affiliated to Iranian universities of medical sciences.